Pengaruh Lama Perendaman E-Glass Fiber Reinforced Composite dalam Obat Kumur Terhadap Kekuatan Fleksural - Hasna Syifa Yuniva; Widowati Siswomihardjo; Siti Sunarintyas (Jurnal Material Kedokteran Gigi, 2019)
Fiber reinforced composite (FRC) is a material consisting of a composite resin (matrix), fiber (reinforced) and silanes (to improve the adhesion strength). FRC can be used as a crown framework. More people used mouthwash for oral hygient. The objective of this study was to know the effect of the duration of E-glass FRC immersion into the mouthwash against the flexural strength. The research materials were E-glass (Fiber Splint Polydentia Multi-Layer, Switzerland), composite resin (Master Flow Biodynamic, Brazil), silane (Monobond Ivoclar Vivadent) and mouthwash (Listerine® Multi Protect). Twelve the beam-shaped specimens (25x2x2) mm The specimens were divided into 3 groups: K1 control group (was not immersed) K2 and K3 treatment groups (was immersed for 24 and 48 hours). The flexural strength value was measured using a universal testing machine (Pearson, Texas). The data were analyzed using one-way ANOVA followed-up by LSD. The results showed decrease of the average flexural strengths of mouthwash K1, K2 and K3. The one-way ANOVA test results showed that there was a significant P>0.05 in the duration of E-glass FRC immersion into the mouthwash against the flexural strength. The LSD test results showed significant differences between all treatment groups. The conclusion of this study is that the duration of E-glass FRC immersion into mouthwash will lower the strength of flexural E-glass FRC.